2014
DOI: 10.1007/s10461-014-0884-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Knowledge of Male Partner HIV Testing and Serostatus Among African-American Women Living in High Poverty, High HIV Prevalence Communities (HPTN 064)

Abstract: Knowledge of sexual partners' HIV infection can reduce risky sexual behaviors. Yet, there are no published studies to-date examining prevalence and characteristics associated with knowledge among African-American women living in high poverty communities disproportionately affected by HIV. Using the HIV Prevention Trial Network's (HPTN) 064 Study data, multivariable logistic regression was used to examine individual, partner, and partnership-level determinants of women's knowledge (n=1,768 women). Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“… 28 The Women's HIV SeroIncidence Study (HPTN 064) examined the prevalence and characteristics associated with knowledge of partner's serostatus among a cohort of African American women in the United States. 29 The study found that 43% of the African American women living in high poverty and high HIV prevalence areas were unaware of their most recent male partner's HIV status. The women with lower knowledge of partner serostatus was associated with having two or more sex partners, suggesting that women most at risk for HIV are least likely to know of their infection risk.…”
Section: Resultsmentioning
confidence: 96%
“… 28 The Women's HIV SeroIncidence Study (HPTN 064) examined the prevalence and characteristics associated with knowledge of partner's serostatus among a cohort of African American women in the United States. 29 The study found that 43% of the African American women living in high poverty and high HIV prevalence areas were unaware of their most recent male partner's HIV status. The women with lower knowledge of partner serostatus was associated with having two or more sex partners, suggesting that women most at risk for HIV are least likely to know of their infection risk.…”
Section: Resultsmentioning
confidence: 96%
“…A growing body of literature suggests that factors such as poverty, perceived discrimination, community-level gender imbalances, housing instability, and witnessed and experienced crime and violence in geographically defined areas contribute to HIV risk [ 13 16 , 42 47 ]. Women in our study described these mediating influences and provided insight on how these issues potentially interact, rendering women vulnerable to HIV acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in predominantly Black/African American communities, the impact of disproportionate incarceration of Black/African American men and the associated mortality from community violence creates an imbalanced female-to-male ratio. Such imbalances thereby reduce women’s opportunity to negotiate sexual monogamy in these circumstances [ 13 16 ]. Managing such relationship challenges, which are often coupled with the stress of providing for children without financial and social support, has been independently linked to individual-level risk factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, knowledge of their partners serostatus, a key component of HIV prevention, is strongly related to financial security and that women with fewer economic resources are less likely to have power in a relationship to negotiate knowledge and protection against HIV. (55) PrEP for these women must combine more than just a pill, but a “behavioral, economic and empowerment approaches are likely to be more effective in addressing the multiplicity of vulnerabilities of this population.…”
Section: Key Issues In Adoption Of Prep For Communitymentioning
confidence: 99%